Smooth traffic flow as one of the most important factors for safety increase in road transport - Kalašová, Alica; Stacho, Milan (Transport, 2006)
The elimination of the connection between the increase of transport and economical growth has been the main aim of transport policy of the EU for a few years, which has not been accomplished yet. The volume of transport in the EU has been growing at more or less the same rate as economy or more, by nearly 20% with passenger transport and by approximately 30% with freight transport haulage. Transportation causes considerable external costs that although have got concrete originators, are not paid by them. The biggest external costs are connected with emissions, noise, accidents and congestions. In our contribution we would like to characterize congestions and possible solutions.First Published Online: 27 Oct 2010